1991
DOI: 10.1091/mbc.2.11.927
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin variants: differential binding to fibronectin and distinct distribution in cell cultures and tissues.

Abstract: In the chicken, three tenascin variants have been characterized that are generated by alternative splicing of 3 of its 11 fibronectin type III repeats. Using monoclonal antibodies that react with common regions versus extra repeats of tenascin, we could distinguish and separate tenascin variants and investigate their interaction with fibronectin using multiple experimental procedures. Interestingly, in all assays used the smallest tenascin variant bound more strongly to fibronectin than the larger ones. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 35 publications
4
91
0
1
Order By: Relevance
“…In chick tissues, the intermediate sized and largest isoforms of Tn-C (containing variable numbers or all alternatively spliced domains, respectively) are known to be distributed in smooth muscle and underneath the epithelial lining of the villi, paralleling our immunohistochemical analysis of human tissues. 49 In a previous study on breast cancers using a conventional Tn-C antibody, it was shown that expression at invasion sites correlates with a higher proliferation rate of cancer cells and is a predictor of local recurrence and metastasis. 13,14 We have showed that Tn-C molecules expressed at the invasion fronts of tumors may chiefly be of the large variant type.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In chick tissues, the intermediate sized and largest isoforms of Tn-C (containing variable numbers or all alternatively spliced domains, respectively) are known to be distributed in smooth muscle and underneath the epithelial lining of the villi, paralleling our immunohistochemical analysis of human tissues. 49 In a previous study on breast cancers using a conventional Tn-C antibody, it was shown that expression at invasion sites correlates with a higher proliferation rate of cancer cells and is a predictor of local recurrence and metastasis. 13,14 We have showed that Tn-C molecules expressed at the invasion fronts of tumors may chiefly be of the large variant type.…”
Section: Discussionmentioning
confidence: 98%
“…The smallest variant (with complete omission of the alternatively spliced region) binds to fibronectin with higher affinity than the large variants and is incorporated into the matrix. 49,50 This difference in binding capability between the Tn-C variants may account for the variation in staining patterns between the two antibodies. In chick tissues, the intermediate sized and largest isoforms of Tn-C (containing variable numbers or all alternatively spliced domains, respectively) are known to be distributed in smooth muscle and underneath the epithelial lining of the villi, paralleling our immunohistochemical analysis of human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…More surprisingly, FibRas cells failed to deposit TN-C in the ECM, although these cells secrete TN-C and produced an ECM containing both FN and perlecan even in the absence of TGFb1 (Figures 3b and 7c). Therefore, oncogenic Ha-Ras not only prevents secretion but also interferes with ECM deposition of TN-C and its direct interaction with FN/perlecan, described in other cell systems (Chiquet-Ehrismann et al, 1991;Chung and Erickson, 1997).…”
Section: Tenascin-c Expression Is Downregulated In Eph4 Cells Upon Epmentioning
confidence: 96%
“…The three isoforms of chick tenascin, Tn230, Tn200, and Tn190, display tissue-specific distributions in vivo (Prieto et al, 1990;Chiquet-Ehrismann et al, 1991). To determine which tenascin isoform was present in the tissues examined above, longitudinal sections of Day 19 chick embryo knee were processed for immunofluorescence using anti-Tn26 and anti-Tn32 monoclonal antibodies (Spring et al, 1989).…”
Section: Tenascin Isoformsmentioning
confidence: 99%
“…Tenascin variants differing in molecular size have been found in both mammals and avians; they are the product of alternative splicing and differ in the number of fibronectin type I11 repeats (Spring et al, 1989;Gulcher et al, 1989;Prieto et al, 1990;Saga et al, 1991;Siri et al, 1991;Weller et al, 1991). In chick the largest tenascin has 13 such repeats and an Mr of 230,000 (Tn230), whereas variants with only nine or eight repeats exhibit Mr's of 200,000 (Tn200) and 190,000 (Tn190), respectively (Spring et al, 1989;Chiquet-Ehrismann et al, 1991).…”
Section: Introductionmentioning
confidence: 99%